Answer:
Simplified = 5
Classification = Monomial
Explanation:
PART I: Simplify the expression
Given expression:
3x² + 6x + 5 - 3x (2 + x)
Expand parenthesis by distributive property:
= 3x² + 6x + 5 - 3x (2) - 3x (x)
= 3x² +6x + 5 - 6x - 3x²
Put like terms together:
= 3x² - 3x² + 6x - 6x + 5
= 0 + 0 + 5
=
PART II: Classify polynomial
Concept:
Polynomial is classified by the number of terms a polynomial has.
- Monomial: a polynomial with only one term
- Binomial: a polynomial with two terms
- ...
Classify the given expression:
Original = 3x² + 6x + 5 - 3x (2 + x)
Simplified = 5
5 is a constant and it has only one term
Therefore, it is a monomial.
Hope this helps!! :)
Please let me know if you have any questions